(3x-1)+(2x+4)=

Simple and best practice solution for (3x-1)+(2x+4)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (3x-1)+(2x+4)= equation:


Simplifying
(3x + -1) + (2x + 4) = 0

Reorder the terms:
(-1 + 3x) + (2x + 4) = 0

Remove parenthesis around (-1 + 3x)
-1 + 3x + (2x + 4) = 0

Reorder the terms:
-1 + 3x + (4 + 2x) = 0

Remove parenthesis around (4 + 2x)
-1 + 3x + 4 + 2x = 0

Reorder the terms:
-1 + 4 + 3x + 2x = 0

Combine like terms: -1 + 4 = 3
3 + 3x + 2x = 0

Combine like terms: 3x + 2x = 5x
3 + 5x = 0

Solving
3 + 5x = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-3' to each side of the equation.
3 + -3 + 5x = 0 + -3

Combine like terms: 3 + -3 = 0
0 + 5x = 0 + -3
5x = 0 + -3

Combine like terms: 0 + -3 = -3
5x = -3

Divide each side by '5'.
x = -0.6

Simplifying
x = -0.6

See similar equations:

| 12x-6=14x+35 | | 6t-2=5t+134 | | -2(4y+15)+8y=5 | | c+c+2c+5+4= | | 2(-2)-y=1 | | 5x-3(2x-1)=5 | | -43-14y+13=-32y+14+7y | | 7y+1=9+3 | | -8v+18=2(v+4) | | 2x^2-2015x+2015=0 | | n(x)=0 | | -7u+3(u-7)=7 | | 3(v+2)+2v=-14 | | (13+2x)-(4-x)= | | 7xln(x)=0 | | 21-y=6 | | 3x(8y-5)= | | -44-8y+14=-21y+45+8 | | (3x-1)x=4 | | 10+2=2 | | 5.345x-x=50 | | 9x^2-45=36x | | 2w^3+54=0 | | 1.1472x-x=50 | | 5y=3-11x | | 3(3y-8)-4y=10 | | y^3+3y+2=0 | | 28-4x=7-7xequation | | 130*0.3048-25t=15 | | 8(m+3)=48 | | 6c-9=36c+20 | | y=60000+1 |

Equations solver categories